Przyczyny i efekty restrukturyzacji zatrudnienia w szpitalach w opinii kadry zarządzającej - Jończyk, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper, concerned with hospital employment restructurization, presents the changes that tookplace in the employment in hospitals in the opinion of managers after the introduction of healthcarereform. The main aim of this study was to describe the causes and effects of employmentrestructurization. The conclusions were based on empirical material collected during author's ownstudy performed in January and February 2006 in 13 hospitals from Podlasie region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 167-173